Design and simulation of infrared photo detectors - Qiu, Feng. (2012)
In 1830, l, debbi Billy using the new found at temperature electric effect (also called plug baker effect), make a with half a metal bismuth and antimony temperature electric dipoles for the thermal type, and the first to detector probe after the birth of the other functions, following the detector successively development. The probe is mainly used for measuring inspection, control tracking, image measurement and analysis, etc. Photovoltaic detector is made using photovoltaic effects of semiconductor devices. This kind of device many kinds, but their principle is same, so in nature have many similar places.